MISI GEREJA SEBAGAI PERSEKUTUAN YANG TERBUKA BERDASARKAN DOA TUHAN YESUS DALAM YOHANES 17:18-19 - Paulus Purwoto (Manna Rafflesia, 2023)
The church founded by the Lord Jesus is an exclusive fellowship in matters of faith and salvation in the Lord Jesus Christ. On the other hand, the church is also an open (inclusive) communion that wants to work with others. The problem is the concept of the church as an open communion and the Biblical open missional paradigm. Using a qualitative descriptive method with a literature and hermeneutic approach, this study aims to explain the concept of the church as an open communion and explain an open missional paradigm based on the prayer of Jesus in John 17:18-19. The results of this study: first, the church as an open community is a union between church members based on the relational unity of the Trinity of God by developing an attitude of solidarity among fellow members and moving beyond the church community based on love. Second, the open missional paradigm manifests in three ways: Jesus is the central mission, the delegation of mission tasks, and sanctification in truth.